The Application of Storytelling Methods in Language Development for Early Childhood - Zulmi, Fadhli; Mardiah, Ainun (STIT Ahlussunnah Bukittinggi, 2025)
This study was motivated by the importance of developing language skills in early childhood, particularly at As-Salam Hutarimbaru Kindergarten in Lembah Melintang District, West Pasaman Regency. Based on the results of observations, it was found that many children were unable to develop their language skills optimally. One of the reasons for this was that teachers often used lecture methods, which made children feel bored and less interested in learning. The research methodology used was qualitative and a case study approach. Based on the research results and data analysis, it can be concluded that: i) The storytelling method was implemented systematically and planned, using media such as picture books and hand puppets that made children more interested and active in learning, ii) There was a significant improvement in children's language skills, marked by their courage to speak, increased vocabulary, and their ability to understand and retell the story, iii) Teachers play an important role in optimizing the storytelling method through creative strategies and collaboration with parents, so that children's language stimulation can also take place at home. The results of this study can be used as preliminary data for future researchers in examining this issue in different contexts and issues.